X-Ray Diffraction Line Profile Analysis of Strongly Textured Thin Films of ZnO - P. Sutta; Q. Jackuliak (Communications - Scientific letters of the University of Zilina, 2003)
ZnO thin films have been deposited on SiO2 -Si and Al-SiO2 -Si substrates by reactive sputtering. X-ray diffractometry was used to determine microstructural disorder parameters in ZnO thin films with strong preferred c-axis orientation. The influence of Al and Al2O3 buffer layer on preferred c-axis orientation and microstrain of crystallites was also studied. The microstrains and domain size showed only a small dependence on the preference of a buffer layer, but they depend on the thickness of ZnO thin film. The stress gradient along the c-axis was observed in all of studied samples.